crumb rubber auction system in KUD Berkat at MUARA ENIM District South Sumatera Province - Pranata, Bagus Dwi; Badrudin, Redy; Romdhon, Muhamad Mustopa (Jurnal AGRISEP, 2020)
Crumb rubber auction is ones of business unit of KUD Berkat, this is the biggest income contribution to the KUD. This research tries to explain the mechanism and the process of lump rubber auction at KUD Berkat. The study was conducted from April to May 2017. Determination of respondents using simple randomg sampling with a total of 58 respondents. The mechanism and process of the auction were explained by descriptive qualitative analysis. The research showed that the mechanism of lump rubber auction starting from rubber farmers to TPK (Cooperative Service Point) is then reported an auction was conducted at KUD Berkat. The factory is given a form to fill the bidding price on several TPK then read the winner of the auction. A week later weighed.